Efektivitas Rumpon Sebagai Struktur Habitat Dalam Menekan Kanibalisme Pada Benih Ikan Baung (Mystus nemurus) Di Kolam Bulat - Sri Murtini; Kadek Adi Suwandana; Neksidin; Selviana Anggraini; Mahadi Suroso (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
This study investigated the effectiveness of artificial shelter structures (rumpon) in reducing cannibalism and improving the survival rate of baung fish (Mystus nemurus) fry cultured in circular ponds. Cannibalism is one of the major constraints in baung fish hatchery production because it significantly decreases fry survival and productivity. A Completely Randomized Design (CRD) consisting of four treatments, namely control (without rumpon), full rumpon, ¾ rumpon, and ½ rumpon, with three replications for each treatment was applied. Parameters observed included survival rate and water quality (temperature, pH, and dissolved oxygen). Data were analyzed using analysis of variance (ANOVA), while water quality parameters were analyzed descriptively. The results showed that the full rumpon treatment produced the highest survival rate (56%), followed by ½ rumpon (50%), ¾ rumpon (45%), and control (13%). The presence of rumpon increased habitat complexity, reduced direct interactions among fry, minimized cannibalistic behavior, and consequently improved survival. This study demonstrates that coconut leaf rumpon can serve as a simple, environmentally friendly, and low-cost habitat modification technology to enhance baung fish hatchery performance.